TULA in recurrent non‐muscle invasive bladder cancer. Issue 1 (27th January 2020) - Sarkar, Somita; Mayor, Nikhil; Mostafid, Hugh
Abstract : Recent NICE guidance says there is limited evidence for the efficacy of transurethral laser ablation for recurrent non‐muscle invasive bladder cancer and that 'special arrangements' need to be in place if it is to be offered to patients. Here the authors consider the advantages and drawbacks of the treatment.